"Seatbelts don't save lives": Discovering and targeting the attitudes and behaviors of young Arab male drivers. (December 2018) - Dun, Susan; Ali, Amal Zeyad
Highlights: Young Arab male drivers are reactive toward typical safe driving messages. Seatbelts are not worn because of wrinkling clothing and friend's derision. A novel, tailored, culturally adapted message changed seatbelt attitudes and beliefs. Fatalism and risky driving aren't related to change in seatbelt attitudes and beliefs. Abstract: The paper presents a two-part study that discovered then targeted beliefs and attitudes towards seatbelt use in young Arab men. The purpose of part one was to discover their safe driving beliefs, attitudes and behaviors as well as their responses to safe driving campaigns to ascertain message elements that could incite reactance. Part two targeted selected beliefs and attitudes in a message that was designed based on the results from part one to both address relevant beliefs and attitudes as well as avoid reactance. One belief, that seatbelts are not necessary in the back seat, and two attitudes, avoidance of wearing the seatbelt to prevent clothing from being wrinkled and to avoid friends' derision, were targeted. Because the participants reported reactance to common safe driving campaigns, the options for the message were quite limited. Using fear appeals, shocking content or depicting the consequences of accidents was deemed likely to be ineffective, rather a novel approach was called for. Utilizing the collectivist and masculine nature of the culture, the resulting message featured a group of young Arab men who are convinced by a personified Seatbelt to wear their seatbelts after an adventure. The message succeeded in eliciting statistically reliable belief and attitudinal change on all three dependent variables after one exposure, suggesting that tailored messages that avoid triggering reactance and are culturally contextualized while aimed at specific beliefs and attitudes can be persuasive. Although risk taking behavior can result from group pressure, our message used culturally specific group pressure but depicted it as being against the risky behavior and positively reinforced the less risky behavior, demonstrating that such approaches can be effective. The film was not a typical safe driving message, utilized social norms from the target audience and was carefully matched to their attitudes and beliefs while not being an overtly persuasive. We argue that message campaigners can utilize both the method and results for subsequent campaigns aimed at young Arab men.